SYNTHESIS AND ANALGESIC ACTIVITY OF 6-(MNITROPHENYL)-4-SUSTITUTED BENZYLIDENE-4,5-DIHYDROPYRIDAZIN-3(2H)-ONE DERIVATIVES - Asif, Mohammad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Many research groups have been interested in 3(2H)-pyridazinones for the development of potential analgesic and antiinflammatory agents. Stimulated by these findings, three 6-(mNitrophenyl)-4-sustituted benzylidene-4,5-dihydropyridazin-3(2H)-ones (IVa-IVc) have been synthesized and evaluated for analgesic activity against hot plate method. Compounds IVa-IVc were prepared from 6-m-nitrophenyl-4,5-pyridazin-3(2H)-one by condensation with respective aldehydes. All compounds (IVa-IVc) having nitro phenyl and benzylidene groups at position 6 and 4 of the pyridazinone ring receptively. All compounds (IVa-IVc) showed significant analgesic activity when compare to control group and were found less potent than reference drug aspirin.Key words:Pyridazinones, analgesic, benzylidene, nitrophenyl.